ANALYSIS OF THE LEVEL OF TRANSFORMING GROWTH FACTOR β1 IN CHILDREN WITH BRONCHIAL ASTHMA - Наталья Леонидовна Потапова; Инесса Никандровна Гаймоленко (The Publishing House Medicine and Enlightenment, 2019)
Achieving control over the symptoms of the disease is the most important and serious task in the treatment of bronchial asthma. The cause of uncontrolled flow may be the activation of tissue growth factors that trigger the process of remodeling the respiratory tract. The aim of the research - to study the change in the level of transforming growth factor β1 in children with bronchial asthma. Materials and methods. The article presents the results of a comprehensive examination of 71 patients aged 1 to 16 years. To determine the level of transforming growth factor β1, a set of reagents for enzyme immunoassay by Vector-best was used. Results. In children with bronchial asthma, the level of profibrotic cytokine significantly increases in the absence of control over asthma symptoms. High values of transforming growth factor β1 positively correlate with obstructive ventilation disorders. Conclusion. Increasing the level of transforming growth factor β1 is a prognostically unfavorable marker of airway remodeling.